Training on Creating LMS Google Sites as an Innovative Learning Media for Elementary School Teachers in West Sumbawa Regency - Hidayat, Sopan; Agung Saputra, Rizka Donny (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This activity aims to enhance the competence of educators in developing Google Sites LMS as an innovative learning medium. The methods used in this training are lectures and demonstrations. The lecture method is employed to provide material on improving teachers' knowledge, competence, and skills in creating Google Sites LMS as an innovative learning medium. Meanwhile, the demonstration method is conducted for participants to directly practice creating learning media using Google Sites. The training participants are 35 elementary school teachers from West Sumbawa Regency. The results of this activity indicate that the training participants received a positive response; they feel more confident and capable of using Google Sites after attending the training. This shows that the training has successfully achieved its main objective, which is to enhance educators' abilities in using information technology to support the learning process. Further training and direct assistance to schools are highly necessary to ensure optimal implementation.